Resistance levels of Spanish conifers against Fusarium circinatum and Diplodia pinea. Issue 6 (5th June 2013) - Iturritxa, E.; Ganley, R. J.; Raposo, R.; García‐Serna, I.; Mesanza, N.; Kirkpatrick, S. C.; Gordon, T. R.; Woodward, S.
Summary Pitch canker, caused by Fusarium circinatum, and Diplodia shoot blight, caused by Diplodia pinea, are both damaging to pines (Pinus spp.) grown in plantations throughout the world, including Spain. To assess the potential for interspecific differences in susceptibility to contribute to the management of pitch canker and Diplodia shoot blight in the Atlantic region of Spain, the present study was undertaken to characterize the susceptibility of six pine species (P. sylvestris, P. nigra, P. pinaster, P. radiata, P. halepensis and P. pinea) and Douglas‐fir (Pseudotsuga menziesii) to F. circinatum and D. pinea. Based on inoculations of 2‐year‐old trees, Ps. menziesii, P. pinea and P. nigra were the most resistant to F. circinatum, with lesion lengths ranging from 3.7 to 21.5 mm, 2.2 to 12.6 mm and 2.8 to 30.9 mm, respectively. At the other extreme, Pinus radiata was the most susceptible, sustaining lesions that ranged from 8.5 to 74.8 mm in length. Pinus sylvestris, P. pinaster and P. halepensis showed an intermediate response to F. circinatum. Broadly similar results were observed in inoculations with D. pinea, with Ps. menziesii being relatively resistant and P. radiata being highly susceptible. Consistent with these results, field surveys revealed no pitch canker in stands of Ps. menziesii and low severity of Diplodia shoot blight, whereas P. radiata was severely affected by both diseases. Our findings suggest that selection of appropriate species can greatly reduce the risk of damage from two important canker diseases affecting pine plantations in the Atlantic region of Spain. Furthermore, intraspecific variation in susceptibility implies that selection may allow for the enhancement of resistance in otherwise susceptible species.